Зміни ліпідних показників у поті осіб, діяльність яких пов'язана з військовою службою - Варус, В.І.; Брюзгіна, Т.С.; Белов, О.А.; Соловська, С.С.; Депутат, Ю.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The changes of the fatty acid composition of lipids of persons' sweat, whose activity is related to a military service, are investigated. The authentic changes are established, which allows ones to use the non-invasive biological object as a criterion of rating the desadaptation processes running in military men.